Gambaran Motivasi Belajar Siswa Pada Pembelajaran Daring di SMK Ma’arif NU 1 Ajibarang - Fitriana Fitriana; Wasis Eko Kurniawan; Arni Nur Rahmawati (Universitas Harapan Bangsa Purwokerto, 2023)
The Covid-19 pandemic has changed the pattern of learning that should be face-to-face to distance learning or commonly called online. Online learning is an educational innovation that involves elements of information technology in learning. Communication between parents and children is very necessary in the educational process. The general purpose of this researcher is to find out the description of student learning motivation in online learning at SMK Ma'arif NU Ajibarang. The research method used is descriptive quantitative with a cross sectional approach. The sampling technique in this study, researchers used proportionate stratified random sampling of 84 respondents. The data analysis used is univariate analysis. The results showed that the most dominant student age was 16 years old (38.1%), with female gender (76.2%) and the most dominant student learning motivation was in the medium category (45.5%). The conclusion is that there is a relationship between family communication patterns and students' learning motivation in online learning at SMK Ma'arif NU Ajibarang.